Sosiodemografi PUS dan Keterpaparan Informasi KB dengan Pilihan Alat Kontrasepsi KB - Lanny Suasana; Retna Mahriani; Nengyanti Nengyanti (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the sociodemographic relationship between PUS and exposure to family planning information with the choice of family planning contraceptives in Prabumulih City. This research method uses a quantitative approach and the 2021 Family Data Collection (PK 21) results. The results showed that jobs with an odds ratio of 80.945 with a significant value of 0.000 and a positive sign for the coefficient indicated that the job had 80.945 times the chance of choosing family planning contraceptives. In conclusion, the most dominant factor influencing the choice of family planning contraceptives is work. Keywords: Family Planning Contraceptives, Exposure to Family Planning Information, Sociodemography